An innovative method and a medical screening device for cancer detection in real-time - K Papageorgiou; G Papageorgiou (Annals of Mathematics and Physics - Peertechz Publications, 2023)
Histopathology is the main technique to assess the presence of cancer cells in biopsy material and for the evaluation of positive resection margins, but it is not real-time. Older methods to assess resection margin intraoperatively are either time-consuming or exhibit a low accuracy. More recent imaging techniques have various drawbacks, like the need for exogenous contrast agents or excessive time to assess the entire resection surface or a low diagnostic performance in detecting certain types of cancer. The purpose of the current research work is the development of a medical screening device for cancer cells detection with very high accuracy and selectivity, based on a newly developed method in order to experimentally measure in real-time the excitation response of the charged elements of the biological tissue under study to the applied alternative electrical field, over a wide range of frequency spectra.  The aim of this study is to present an innovative method and results from a prototype medical screening device, which allows the selective and "real-time" detection of cancer cells of any type among normal cells in any tissue type.  The innovation of the proposed method lies in the view of the cell membrane emulation as an electrical circuit and also in the ability to experimentally measure in real-time the excitation response of the charged elements of the biological tissue under studies like ions, interfaces or dipoles to the applied alternative electrical field, over a wide range of frequency spectra according to the dielectric spectroscopy method. The ions can very easily follow the variations of the applied alternating electric field moving along the dynamic lines of the field. In contrast, the incapability of the abnormal neoplastic cellular formations to follow the frequency changes causes them to perform dipole oscillation instead of moving along the dynamic lines of the field. This experimentally appears as a significant increase of the capacitive component contribution to the total impedance of the tissue, relative to the purely electrical resistance contribution of the ions. A model, backed by the relevant mathematical equations, has been developed to integrate the unknown impedance of both the tissue under assessment and the interdigital micro-sensor with the known complex impedance of the data acquisition system. The ability to selectively detect cancer cells has an obvious interest and various applications in cancer diagnosis and therapy.